Assessment of Trees Outside Forest (TOF) in Selected Makiling Subwatersheds - Jan Joseph V. Dida; Joseph C. Paquit; Cheamson Garret K. Boongaling; Gemmalyn E. Magnaye; Nathaniel C. Bantayan (International Journal of Agriculture System, 2013)
Trees outside Forest (TOF) are trees, shrubs, bushes including palms that are found in the Food and Agriculture Organization (FAO) other land classification that can be agricultural, urban, or non-agricultural/urban. TOF provide various services and functions that are neither well documented nor given enough attention, hence the need to identify and assess them in agriculture and urban areas outside Mt. Makiling. A SPOT satellite image (2010) covering the Cambantoc, Molawin-Dampalit, and Tigbi subwatersheds of Mt. Makiling was used in the supervised classification of forests, lakes, agriculture, and urban areas. Areas that qualify as other lands were extracted using the classified land types as guides in GIS vector format. Using Google Earth imagery, other lands were digitized and assessed following the FAO decision tree algorithm for TOF and field checking was conducted to validate the tree height in the TOF criteria. Based on the GIS and field assessment, Tigbi and Molawin-Dampalit were found to have TOF on urban land that are mostly fruit trees cultivated for food, landscaping while Cambantoc has TOF on agricultural land and TOF on non-agricultural/urban that are used as farm windbreaks. Findings suggested that TOF contributed to the tree canopy cover in Makiling subwatersheds. Assessment of TOF can be used to account for the ecosystem services it provides which complement those that come from forests and other wooded lands. FAO also recognizes the importance of TOF for local and national food security. TOF, especially fruit trees, are important source of food products for the people.